Partición de nutrientes en árboles de Nothofagus antárctica creciendo en un gradiente de calidades de sitio en Patagonia Sur. - Gargaglione, Verónica (2013)
Nothofagus antarctica is a native species that grows in the South of Argentina and Chile. Information of tree nutrient partitioning is essential for evaluating the impacts of silvicultural practices on site productivity, mineral fertility and bioelement recycling. We determined nitrogen, phosphorous, potassium, calcium, sulphur and magnesium partition in plant organs (i.e. root, stem, foliage) by allometric relationships of nutrient partitioning among aerial and below ground N. antarctica components. We used information previously reported of nutrient contents of individual trees across different ages (5-220 years) and crown classes (dominant, codominant, intermediate and suppressed) growing on different site classes. Allometric regressions were fitted for nitrogen, phosphorus, potassium, calcium, sulphur and magnesium aerial-belowground, leaves-roots, stems-roots and leaves-stems. Slopes were compared by ANOVA to detect differences according to site classes. Allometric regression analyses for nutrient partitioning showed good fitness (R2 between 0.77 and 0.99) and allocation varied depending on each particular nutrient and site class. For example, in the best site class, magnesium was the most allocated to aerial components; meanwhile in the worst site the gradient calcium > nitrogen > magnesium > phosphorus = potassium = sulphur was found. Furthermore, all allometric relationships that included roots had lower slopes for worse site classes, indicating higher nutrient allocation to belowground components. Roots were an important sink for most nutrients, and its relative importance increased as site quality decreased. This characteristic to differently allocate resources according to site could be the explanation for the broad distribution of N. antarctica in Patagonia, from wet to drier sites.